A modified Direct Strength Method for nonlinear twisting model of simply-supported C-section purlins. (November 2018) - Bai, Fan; Yang, Na; Zhang, Hao; Wang, Xiaofeng
Abstract: This paper proposes a framework to predict the buckling limit states of C-section purlins under wind uplift load with top flange restrained by the sheeting. The prediction framework includes a nonlinear twisting model to account for the flexural-torsional behavior and the application on the Direct Strength Method. The torsional effect induced by load eccentricity and the diaphragm effects provided by sheeting are incorporated into the flexural-torsional differential equations of the nonlinear twisting model. The biaxial bending moments and bi-moment, the flexural-torsional buckling strength and the stress distribution of the purlin can be obtained from the proposed model. On the basis of the Finite Strip Method (FSM), the elastic buckling load can be calculated through reducing the applied bending moments by the load factor. Thereafter, the Direct Strength Method is modified to account for the buckling interaction behavior influenced by the warping-torsion and diaphragm effects. A database of 17 simple-span purlin tests is used to validate the proposed model. Graphical abstract: Unlabelled Image Highlights: Proposed a nonlinear twisting model to calculate the biaxial bending moments and bi-moment. Elastic buckling load can be obtained based on the biaxial bending moments and bi-moment combined with FSM. Proposed a modified Direct Strength Method to account for the interaction behavior considering the diaphragm effects.